The Nuts and Bolts of Copyright. Circular R1 - Library of Congress, Washington, DC. Copyright Office; Library of Congress, Washington, DC. Copyright Office ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This general guide to copyright in the United States briefly describes the following: the nature of copyright, who can claim it, copyright available for published and unpublished works, what can and cannot be copyrighted, how to secure a copyright, publication, notice of copyright, copyright registration, registration procedures, corrections or amplifications of existing registrations, mandatory deposit, duration of copyright, transfer of copyright, international copyright protection, application forms, mailing instructions, fees, and sources of further information. (FM)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402 (1979-311-426/25).
ERIC Note: Contains colored print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Copyrights; Eligibility; Federal Legislation; Federal Regulation; Guidelines; Publications; Guides, General; Legal/Legislative/Regulatory Materials